The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1093/ntr/ntq018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bupropion on simulated demand for cigarettes and the subjective effects of smoking

Abstract: Introduction: The biobehavioral mechanism(s) mediating bupropion's efficacy are not well understood. Behavioral economic measures such as demand curves have proven useful in investigations of the reinforcing effects of drugs of abuse. Behavioral economic measures may also be used to measure the effect of pharmacotherapies on the reinforcing effects of drugs of abuse. Methods:The effects of bupropion on simulated demand for cigarettes were investigated in a placebo-controlled doubleblind clinical trial. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 44 publications
4
50
0
Order By: Relevance
“…Although HPTs are becoming increasingly popular in behavioral economic research on addictions (Bickel et al, 2011;Bickel et al, 2014;Jarmolowicz et al, 2016) and behavioral health in general , as of yet only one study has validated the TPT against two commonly used questionnaires in substance use disorder research. Given the growing number of validation studies in the substance use literature (e.g., alcohol and tobacco; Amlung et al, 2012;Amlung & MacKillop, 2014;Amlung et al, 2015;MacKillop et al, 2007;MacKillop & Lisman, 2008;MacKillop et al, 2010;Madden & Kalman, 2010), future research may attempt to validate the TPT with tanning specific addiction tools such as the Structured Interview for Tanning Abuse and Dependence (Hillhouse, Baker, Turrisi, Shields, Stapleton, Jain, & Longacre, 2012), the Tanning Pathology Scale (Heckman et al, 2014;Hillhouse et al, 2010), and experiential tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Although HPTs are becoming increasingly popular in behavioral economic research on addictions (Bickel et al, 2011;Bickel et al, 2014;Jarmolowicz et al, 2016) and behavioral health in general , as of yet only one study has validated the TPT against two commonly used questionnaires in substance use disorder research. Given the growing number of validation studies in the substance use literature (e.g., alcohol and tobacco; Amlung et al, 2012;Amlung & MacKillop, 2014;Amlung et al, 2015;MacKillop et al, 2007;MacKillop & Lisman, 2008;MacKillop et al, 2010;Madden & Kalman, 2010), future research may attempt to validate the TPT with tanning specific addiction tools such as the Structured Interview for Tanning Abuse and Dependence (Hillhouse, Baker, Turrisi, Shields, Stapleton, Jain, & Longacre, 2012), the Tanning Pathology Scale (Heckman et al, 2014;Hillhouse et al, 2010), and experiential tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The Cigarette Purchase Task (CPT ; MacKillop et al, 2008 ) is based on a model of drug reward assessment that has been successfully used with several drugs including heroin ( Jacobs & Bickel, 1999 ;Petry & Bickel, 1998 ), tobacco ( Jacobs & Bickel, 1999 ;MacKillop et al, 2008 ;Madden & Kalman, 2010 ), and alcohol ( MacKillop et al, 2008 ;Murphy & MacKillop, 2006 ;Murphy, MacKillop, Skidmore, & Pederson, 2009 ). Participants indicated how many cigarettes they would purchase at each of the following 18 prices: 0.01, 0.5, 0.1, 0.3, 0.5, 1,2,3,4,5,6,11,35,70,140,280,560, and 1120 US $ / cigarette.…”
Section: Nicotine and Tobacco Researchmentioning
confidence: 99%
“…Another possible explanation for the CPT results is that the smoker becomes , generally , more sensitive to price for any commodity, which could also be tested by including other choice options besides cigarettes in future studies. Interestingly, a recent study showed that bupropion had no effect on demand elasticity or demand intensity for cigarettes ( Madden & Kalman, 2010 ), which suggests that this effect may be unique to varenicline.…”
Section: Smoking Rewardmentioning
confidence: 99%
“…The CPT has been increasingly used to examine smoking reinforcement (e.g., Bidwell et al, 2012; MacKillop et al, 2008; Madden & Kalman, 2010) to address questions ranging from reliability of the CPT (Few et al, 2011) to evaluating the impact of changes in tobacco control policy (MacKillop et al, 2012; O'Connor et al, 2012). In a recent clinical trial, Madden and Kalman (2010) found that greater increases in elasticity during the week prior to a quit attempt were associated with greater success in quitting.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent clinical trial, Madden and Kalman (2010) found that greater increases in elasticity during the week prior to a quit attempt were associated with greater success in quitting. These data broadly support the predictive validity of the CPT; however, bupropion had no effect on CPT reinforcement parameters.…”
Section: Introductionmentioning
confidence: 99%